Refugee Theater and Its Transgressions: Acts of Suspension in Joe Murphy and Joe Robertson’s The Jungle - Anna Street (Sillages Critiques)
Following a summary account of the principal challenges faced by theatrical representations of the immigrant’s plight, this article provides a close-reading analysis of Joe Murphy and Joe Robertson’s play The Jungle and its attempts to recreate a restaurant that existed in the refugee and migrant camp in Calais by the same name. It questions how theatrical representation can rise to the task of self-disavowal while retaining its urgency. By focusing on the myriad obstacles to be overcome both in the use of theatre within refugee workshop settings and upon major-venue stages, this approach highlights theater’s extraordinary double-bind in these contexts, offering a reading of The Jungle that foregrounds theater’s transgressive capacity to stage its own renunciation, thus freeing representation from many of its self-inflicted limitations.